Chapter Releasing the Prisoners of Hope: Dante's Purgatorio Breaks the Chains of the Born Frees - Houliston, Victor (Studi e saggi, 2021)
Beginning with a tribute to the late Chris 'Zithulele' Mann, a poet and activist who was deeply immersed in Dante, this chapter comments on some of the patterns that emerge from the creative contributions of the Dantessa students. Two authors affirm and explore ideas of black womanhood by appealing to Beatrice and Francesca, potentially combining the two figures. Several authors are acutely aware of the purgatorial condition of post-apartheid South Africa, suggesting a long and arduous march to freedom. The image of flight recurs: thrice, madly, into the inferno and once, temporarily, in limbo. These lively responses to La Commedia prompt the question: what kind of literary studies is proper to purgatory, and elicit a tentative reply, urging a re-invention of the discipline of letters.